A rapid DNA screening method using high-resolution melt analysis to detect putative Schistosoma haematobium and Schistosoma mattheei hybrids alongside other introgressing schistosomes - Cunningham, Lucas J.; Kayuni, Sekeleghe; Juhász, Alexandra; Makaula, Peter; Lally, David; Namacha, Gladys; Kapira, Donales; Chammudzi, Priscilla; Mainga, Bright; Jones, Sam; Archer, John; LaCourse, E. James; et al. (Frontiers in Tropical Diseases, 2024)
BackgroundThe phenomenon of hybridisation between Schistosoma species has gained a greater degree of significance since the WHO declared that schistosomiasis is to be eliminated, as a public health problem, by 2030. The role hybridisation plays in the transmission of disease is poorly understood and has the potential to complicate this elimination effort. A primary reason for this incomplete understanding of schistosome hybridisation is the lack of suitable, high-throughput and easily accessible methods capable of identifying the species-parentage of individual schistosomes. To address this resource gap, we present the development of a two-tube HRM assay capable of differentiating the species-parentage of schistosomes from a possible range of six species, namely: S. mattheei, S. curassoni, S. bovis, S. haematobium, S. mansoni and S. margrebowiei.MethodsThe assay was designed using aligned reference sequences for the six target species, with primers designed to amplify PCR products with species-specific melt temperatures for both the nuclear and mitochondrial genomes. The sensitivity and specificity of these novel primer sets were tested against a DNA library comprising representatives of: S. mattheei, S. curassoni, S. bovis, S. haematobium, S. mansoni and S. margrebowiei. The optimal annealing temperature for the real-time PCR (rtPCR) assays was established alongside the efficiency for the different primer pairs. The novel HRM assay was trialled against field samples comprising pooled urine from school-age children collected from 13 schools and miracidial samples preserved on FTA cards. Throughout the optimisation and testing of the novel HRM rtPCR primers targeting nDNA and mtDNA markers comparison against a pre-published S. mansoni and S. haematobium probe-based rtPCR was carried out.ResultsThe assay has a comparable sensitivity to current, probe-based species-specific assays and can detect target DNA at concentrations of 1pg/µL-0.1pg/µL for all six species, with the exception for S. bovis which has a slightly lower sensitivity range of 0.1ng/µL-0.1pg/µL. The analysis of the field samples resulted in all pooled urine samples testing positive for S. haematobium and a further three positive for S. mansoni using the probe-based rtPCR. The HRM rtPCR identified four S. mansoni positive samples in addition to six samples identified as being positive for S. mattheei. Despite identifying non-S. haematobium markers in the urine filter samples analysis of the miracidial samples stored on the FTA cards only identified pure S. haematobium.ConclusionAlthough no hybrids were detected in this manuscript the novel-two tube assay described, offers the potential to radically increase the number of samples screened for the presence of hybrids in a range of sample types, including biopsy material for FGS screening. This will result in a decrease in cost and time in identifying putative hybrid cases.